Can green transport policy drive urban carbon emission reduction? Evidence from pilot cities of China’s low−carbon transportation system - Sun, Jian (Frontiers in Environmental Science, 2025)
IntroductionAmidst the global climate crisis and the urgent need for carbon reduction, the transportation sector, a critical source of carbon emissions, has become a focal point for low-carbon transformation.MethodsThis paper investigates the impact of China’s Low-Carbon Transportation System (LCTS) pilot policy on urban carbon emissions using a difference-in-differences (DID) model and a panel dataset covering 242 Chinese cities from 2007 to 2022.ResultsWe find that the LCTS pilot policy has significantly reduced urban carbon emission intensity by an average of 17.3%, highlighting its effectiveness in promoting urban carbon reduction. Mechanism analysis reveals that the LCTS pilot policy achieves emission reduction primarily by fostering green technological development, advancing the clean energy transition, and enhancing government environmental attention. Furthermore, heterogeneous analysis indicates that the policy’s effectiveness is more pronounced in cities with higher public environmental awareness, denser road networks, and stronger public transportation service capabilities.DiscussionThese findings offer valuable insights for the future design and implementation of green transportation policies, providing both theoretical support and empirical evidence for advancing the low-carbon transition in urban transportation sectors. This research contributes to the global efforts in achieving carbon neutrality and offers a reference for other countries and regions aiming to reduce carbon emissions in the transportation sector.